Accounting for the interference component in the technical channel of information leakage of spurious electromagnetic radiation in the video path with diversity reception - Воронов, В.Р.; Заболотний, В.І.; Лиско, В.І. (Radiotekhnika, 2020)
National standards of Ukraine, other legal documents of the system of technical protection of information propose to protect information that is a state and other secret on the objects of information activities of organizations and institutions of all forms of ownership. One of the dangerous technical channels of information leakage is the channel of incidental electromagnetic radiation of the video path of electronic computing equipment. An important element of such a channel is the means of radio and radio intelligence used by the stakeholder to intercept spurious electromagnetic radiation. Intelligence tools are evolving and improving. One of the ways to improve the use of intelligence is the remote reception of incidental electromagnetic radiation. When assessing the possibilities of spaced reception, it is also necessary to take into account the phenomena of interference of the signal reflected from the earth’s surface with the signal of direct propagation from the computer to the reconnaissance antennas. The article is devoted to the analysis of the need to take into account the interference multiplier of electromagnetic field propagation when estimating the possibility of conducting reconnaissance of incidental electromagnetic radiation at spaced reception. Approaches to take into account the factors influencing the interference of PEMV are identified. The components of the quantitative model of the technical channel of information leakage are proposed, which allow taking into account the factors influencing the signal/noise ratio of the signal perceived by the intelligence equipment.